2020
DOI: 10.1002/cpe.5787
|View full text |Cite
|
Sign up to set email alerts
|

Threshold identity authentication signature: Impersonation prevention in social network services

Abstract: Summary While the social network services (SNS) have dominate the ways that people communicate with each other on the Internet, identity impersonation remains to be a serious issue that needs to be solved due to the anonymity in the cyber network. Currently, the potential solution to the problem relies heavily on the administration from the central server, which requires intensive workload of the identity management. In this article, we propose a threshold identity authentication signature scheme to solve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…That is to say, the results of interactions with smart contract are always immediately confirmed at the next block, which is theoretically the fastest response for a blockchain application. In addition, regarding the time cost of off-chain parts like generating signature shares, Chen already demonstrated that they cost an acceptable time for an individual without blockchain in his paper [2]. Therefore, it is not a concern in this paper.…”
Section: Performance Analysismentioning
confidence: 90%
See 4 more Smart Citations
“…That is to say, the results of interactions with smart contract are always immediately confirmed at the next block, which is theoretically the fastest response for a blockchain application. In addition, regarding the time cost of off-chain parts like generating signature shares, Chen already demonstrated that they cost an acceptable time for an individual without blockchain in his paper [2]. Therefore, it is not a concern in this paper.…”
Section: Performance Analysismentioning
confidence: 90%
“…Therefore, SNS only needs to authenticate a very small number of users. Apart from that, smart contract also takes the role of the verifier, while in [2] the verification has to be done by users repeatedly. From the evaluation of gas and time costs, our scheme is proved to be acceptable for nowadays SNS applications.…”
Section: Contributionmentioning
confidence: 99%
See 3 more Smart Citations